Determinación de las diferencias colorimétricas de los esmaltes A1 y A2 comparando 5 marcas de resinas nanohíbridas usando las escalas RGB y CIELAB - Diana Marcela Vera Soto; Dana Michelle Diaz Iriarte (Universidad Antonio Nariño, 2024)
The current work is an experimental type study, intends to determine the colorimetric difference of five different brands of commercial resins, allowing a better overview the professional and granting him a better approach at the time of selecting composite resins.